Swarm intelligence algorithms : a tutorial - Slowik, Adam (CRC Press, Taylor & Francis Group, 2021)
"This book thoroughly presents the basics of 24 algorithms selected from the entire family of swarm intelligence algorithms. Each chapter deals with a different algorithm describing it in detail and showing how it works in the form of a pseudo-code. In addition, the source code is provided for each algorithm in Matlab and in the C ++ programming language. In order to better understand how each swarm intelligence algorithm works, a simple numerical example is included in each chapter, which guides the reader step by step through the individual stages of the algorithm, showing all necessary calculations"- Resumé vydavatele
First edition published 2020
Keywords: inteligence hejna; algoritmy; matematická optimalizace; swarm intelligence; algorithms; mathematical optimization; kolektivní monografie; collective monographs